Análise de desempenho em jogos de wheelchair para-badminton - Ribeiro, Wendel de Oliveira Mota (2019)
The para-badminton is a modality still young in the sporting world context. Much of this, it presents an open field for the sports sciences. One of the most outstanding aspects of sports science today is performance analysis, because it provides support for coaches and athletes to outline training and competition strategies in order to obtain the best possible result. As a result, this dissertation, organized in two independent studies, aimed at analyzing the characteristics of wheelchair para-badminton matches. In the paradeport the number of athletes is not so great, in study 1, 23 matches were analyzed, from the classes (WH1: n = 10; WH2: n = 13), composed by the elite of athletes of the Brazilian wheelchair para-badminton in the simple modality men in the national competition, resulting in the recording and analysis of 6,807 strokes, in addition to the temporal characteristics such as rally times and rest intervals. The technical and temporal variables were compared between the classes, using the t test for independent samples or the Mann-Whitney U test, when necessary. As results we identified that, considering the temporal variables: work load, work density, total time and rally time, WH2 class matches were more intense than WH1 (p <0.005). The net-shot stroke was the only one that presented a difference between classes, with a higher value for WH2 (p <0.001; ES: large). The clear and net-lift strokes correspond approximately to two-thirds of all performed by both classes. The front of the court was the most vulnerable through drop-shot (WH1 = 28%) and net-shot (WH2 = 24%) points. In study 2, 52 games were analyzed, from the same sample of study 1, adding 2 games in class WH2, then the classification of three types of game levels (balanced, unbalanced and very unbalanced) was performed through the difference of score and cluster analysis, and to estimate how much each winning point influenced the results of games, binary logistic regression was used, in addition, discriminant analysis was used to verify which variables discriminated the winners. Finally, tactical sequences of the last three strokes were scored and classified (stroke-response-winning point), according to the target zones of the strokes. As for the results of the games level, the unbalanced level was the most frequent for both classes. The net-lift (OR = 2.9), and the winning point generated by net-lift (OR = 6.8) and drop-shot (OR = 4.8) were the variables that best estimated the odds of victory in the games. Discriminant analysis confirmed the importance of net-lift as a differential factor for victory (CE = 0.33, p = 0.001). We conclude that the WH1 and WH2 classes differentiate the intensity of the match and the greater use of net-lift throughout the game and the winning points obtained through the net-lift and drop-shot scoring are the factors that best estimate the chances of victory. Finally, tactical responses to the middle zone of the court, taking into account the opponent's blow can increase the chances of victory.